Sensitive HPV detection in oropharyngeal cancers - Winder, D.M.; Ball, S.L.R.; Vaughan, K.; Hanna, N.; Woo, Y.L.; Franzer, Y.T.; Sterling, J.C.; Stanley, M.A.; Sudhoff, H.; Goon, P.K.C. (BioMed Central, 2009)
Background Human papillomaviruses (HPV) are the aetiological agents of certain benign and malignant tumours of skin and mucosae; the most important of which is cervical cancer. Also, the incidence of ano-genital warts, HPV-anal cancer and oropharyngeal cancers are rising. To help ascertain a useful PCR detection protocol for oropharyngeal cancers, we directly compared three commonly used primer sets in detection of HPV from different clinical samples.